Effect of bromelain on periodontal destruction and alveolar bone in rats with experimental periodontitis - ÇETİNEL, ŞULE (My University, 2023)
Purpose: Several substances that have anti-inflammatory, antiproteinase, and anti-infective properties have been evaluated as modulators of the inflammatory response in periodontal disease. However, evidence for the anti-inflammatory and antioxidative activities of bromelain is limited. This study evaluated the impact of systemically administered bromelain on the progression of experimental periodontitis. Methods: Four equal groups of 32 Wistar albino rats were created as follows (n = 8): control, periodontitis + saline, periodontitis + 5 mg/kg/day bromelain, and periodontitis + 10 mg/kg/day bromelain. To quantify the resorption of bone and bone volume/tissue volume, bone surface / bone volume, and connectivity, lower jawbones were fixed and then scanned using microcomputed tomography (micro CT). Blood samples were taken to measure the macrophage colony-stimulating factor(M-CSF) concentrations, receptor activator of nuclear factor kappa-Β ligand (RANKL), osteoprotegerin (OPG), tumor necrosis factor-alpha (TNF-α), matrix metalloproteinase-8 (MMP-8), interleukin-6(IL-6), glutathione peroxidase (GPx), superoxide dismutase (SOD), and malondialdehyde (MDA). Histopathological assessments were made to examine the tissue. Results: Treatment with bromelain improved the healing of the periodontium by decreasing the number of leukocytes and ligament deterioration in the gingival connective tissue and by supporting reintegration with alveolar bone. Bromelain used in ligature-induced periodontitis reduced alveolar bone (AB) resorption as measured by microCT; reduced inflammatory parameters such as IL-6 and TNF-α; regulated oxidative-antioxidative processes by increasing GPx and SOD and reducing MDA levels; and regulated AB modeling by decreasing M-CSF, RANKL, and MMP-8 and increasing OPG levels. Conclusion: Bromelain may be an option in periodontal therapy by regulating cytokine levels, improving the healing process, and reducing bone resorption and oxidative stress.
Keywords: Tıp; Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; Farmakoloji ve Toksikoloji; ALERJİ; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; PHARMACOLOGY & TOXICOLOGY; ALLERGY; PHARMACOLOGY & PHARMACY; İmmünoloji ve Alerji; Farmakoloji; Immunology and Allergy; Immunology; Pharmacology; Alveolar bone loss; Antioxidant; Bromelain; Periodontal diseases; Rats